Collaborative care in 'Youth One Stop Shops' in New Zealand: Hidden, time-consuming, essential. (June 2020) - Garrett, Susan; Pullon, Susan; Morgan, Sonya; McKinlay, Eileen
Young people in New Zealand have high morbidity but low service utilization rates. Dedicated youth services 'Youth One Stop Shops' provide 'wraparound' health and social care. However, little is understood about how staff within these services interact with each other or with external agencies to provide this specialist care. This article reports on volume and type of internal and inter-agency health and social service staff–staff interactions, to better understand elements of potential collaboration in day-to-day practice. An observational, case-study approach was utilized. Four dedicated youth services recorded data over three-month periods about a selected number of high-use clients. Youth service staff recorded all interactions with colleagues within their organization and staff from external services. A large volume of non-patient contact work was revealed, with a high proportion of 'complex/involved' interactions recorded. The range and diversity of external agencies with which youth service staff interacted with to meet the needs of young people was extensive and complex. The focus on 'information sharing' and 'complex/involved' interactions demonstrates a well-coordinated, wraparound service delivery model. Current funding formulae take inadequate account of the volume of non-patient contact work that youth services provide for high-needs young people.